Operations Research and Enterprise Systems : 6th International Conference, ICORES 2017, Porto, Portugal, February 23-25, 2017, Revised selected papers /: 6th International Conference, ICORES 2017, Porto, Portugal, February 23-25, 2017, Revised selected papers. (2018) - Unknown
No abstract available